Wireless Mobile Attendance System / Mohd Hariz Naim - Naim, Mohd Hariz (2012)
Wireless Mobile Attendance system is a system that acts as alternative to current attendance system that staffs of FSKM use. It main functionality is to provide wireless signing for work in or work out rather than staffs have to walk to the signing machine. The system is very helpful especially for staffs with less capability and also for pregnant staffs. For the mean time being, the system will be used by staffs at FSKM before being implemented on the whole campus.